Student Satisfaction through Service Quality A Review on Higher Education Sector - Chandramohan, Sandrasekaran (Archives of Business Research, 2019)
Student satisfaction is a key indicator for a higher educational institutional success. As Sri Lanka is envisioning to become a global educational hub this paper attempts to find the key features of the student satisfaction. The service quality model has been applied to identify the students’ satisfaction in the private higher education institutions in Sri Lanka. Theoretical and empirical work studies were used in the conceptualization of the process and a comparability investigation carried out in three international educational regions in order to identify Sri Lanka’s future focus in developing the students’ satisfaction in higher education and thereby becoming a global educational hub as envisioned. Study identifies the global landscape and perception on student satisfaction has significantly been shifted from the fundamental satisfaction indicators. High student mobility and digital learning and teaching mechanism are identified as some of the important parameters for the student satisfaction in higher education institutes.